2018
DOI: 10.1002/qj.3187
|View full text |Cite
|
Sign up to set email alerts
|

The role of heating and cooling associated with ice processes on tropical cyclogenesis and intensification

Abstract: A recent idealized numerical study of tropical cyclogenesis and subsequent intensification using warm‐rain‐only microphysics is extended to examine the modifications brought about by a representation of ice processes. It is found that the time taken to reach cyclogenesis is more than twice that in the equivalent warm‐rain‐only simulation. The subtle reasons for the difference in the length of the gestation period are discussed. A mid‐level vortex forms during the early gestation period when ice processes are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 65 publications
(92 reference statements)
8
33
0
Order By: Relevance
“…The enhancement of the midlevel vorticity usually corresponded to the decrease of the low‐level vorticity, suggesting that the development of midtropospheric vortex was unfavorable for the strengthening of the low‐level circulation. This is consistent with the idealized numerical simulations performed by Kilroy et al (), showing that the time taken to reach cyclogenesis in the experiment with midlevel vortex developed is more than twice that in the equivalent warm‐rain‐only simulation without midlevel vortex. Overall, the vorticity reductions were smaller than the positive vorticity increments in the lower and middle troposphere during the gestation of Nepartak.…”
Section: Evolution Of the Midtropospheric Vortex During The Formationsupporting
confidence: 91%
See 1 more Smart Citation
“…The enhancement of the midlevel vorticity usually corresponded to the decrease of the low‐level vorticity, suggesting that the development of midtropospheric vortex was unfavorable for the strengthening of the low‐level circulation. This is consistent with the idealized numerical simulations performed by Kilroy et al (), showing that the time taken to reach cyclogenesis in the experiment with midlevel vortex developed is more than twice that in the equivalent warm‐rain‐only simulation without midlevel vortex. Overall, the vorticity reductions were smaller than the positive vorticity increments in the lower and middle troposphere during the gestation of Nepartak.…”
Section: Evolution Of the Midtropospheric Vortex During The Formationsupporting
confidence: 91%
“…Although the midtropospheric cyclonic vortex in TC genesis has been paid lots of attention, a consensus is still lacking on the role of midlevel vortex in tropical cyclogenesis. Recently, Kilroy et al (2017Kilroy et al ( , 2018 showed that the tropical cyclogenesis can occur without the existence of a midtropospheric vortex and the rapid organizations of the low-level vorticity in the experiments with or without midlevel vortex are similar. In this work, the formation of Super Typhoon Nepartak (2016) is to be investigated with the focus on the evolution and the role of midtroposheric vortex during the TC genesis.…”
Section: Introductionmentioning
confidence: 96%
“…There are, of course, differences in detail between corresponding experiments associated with the stochastic nature of deep convection (Nguyen et al, ). As in all our recent idealized studies of tropical cyclogenesis (Kilroy et al, ; ; ), deep cumulus convection and the convectively‐induced vertical vorticity distribution are highly nonaxisymmetric, especially before and during much of the early RI phase. As a result, the emerging vorticity monopole retains a degree of relatively strong asymmetry during this stage.…”
Section: Resultsmentioning
confidence: 99%
“…In the idealized simulations by Kilroy et al . (; ; ) and Steenkamp et al . (), genesis was considered to have occurred at the end of a gestation period in which the maximum azimuthally‐averaged tangential wind speed, Vnormalmax, increased only slowly and when this wind speed began a sharp increase.…”
Section: Introductionmentioning
confidence: 93%
“…However, there is disagreement about the role of and processes responsible for the mid-level vortex in TC spin-up, with some recent studies showing that spin-up occurs more rapidly in a simulation where mid-level vortex formation was suppressed by eliminating ice processes (e.g. Lussier et al, 2014;Kilroy et al, 2018) and other studies reporting the absence of TD formation when the latent heat of fusion due to depositional ice growth is removed (Cecelski and Zhang, 2016).…”
Section: Introductionmentioning
confidence: 99%